2009
DOI: 10.1021/cg800351d
|View full text |Cite
|
Sign up to set email alerts
|

Growth Thermodynamics of Nanoscaled α-Alumina Crystallites

Abstract: The growth thermodynamics of nanoscaled α-Al2O3 crystallites after its formation from θ-Al2O3 phase transition by thermal treatment was examined. The crystallite growth characterized with quantized size increments can be performed through coalescence processes. The α-Al2O3 nuclei with sizes 17−20 nm (d cα) coalesced to form α-crystallites of sizes 45−50 nm (d p), then by coalescence of which the stable α-crystallites (d s) with minimum sizes 75−80 nm were obtained. Coalescence of the d s crystallites leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…[27][28][29][30] Thus, the thermodynamic stability of the crystallites is related to their volume and surface free energies. 26 Based on this, the diameter and length that make up the volume and surface of the nanofiber crystallites could presumably experience certain limitations. The length-to-diameter ratios of the nanofibers were briefly examined.…”
Section: Electrospinning Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] Thus, the thermodynamic stability of the crystallites is related to their volume and surface free energies. 26 Based on this, the diameter and length that make up the volume and surface of the nanofiber crystallites could presumably experience certain limitations. The length-to-diameter ratios of the nanofibers were briefly examined.…”
Section: Electrospinning Conditionsmentioning
confidence: 99%
“…(9) and (8) is proposed in this study using values of γ and Gv that have been reported previously. 26,40,41 The surface and volume free energies ofAl 2 O 3 are taken as 2.16 J/m 2 and −73.316 × 10 9 J/m 3 , and those of ␣-Al 2 O 3 are 2.64 J/m 2 and −73.429 × 10 9 J/m 3 . Fig.…”
Section: Thermodynamic Descriptionmentioning
confidence: 99%
“…The transformation is always accompanied with the formation of vermicular microstructures, substantial grain growth and, hence, a great surface area loss. Better understandings of both the a-phase formation and grain growth during the process are of crucial importance to be able to prepare nanocrystalline a-Al 2 O 3 powders, but neither process is well clarified [3].…”
mentioning
confidence: 99%
“…4). As a-Fe 2 O 3 has the corundum structure such as a-Al 2 O 3 , the a-Al 2 O 3 /a- nanoparticles, 16 which may stabilize a-Al 2 O 3 nanoparticles embedded in a-Fe 2 O 3 matrix and conduce to the formation of a-Al 2 O 3 nanoparticles smaller than 12 nm. Because of a too low content of a-Al 2 O 3 in the composite, the XRD pattern of the product calcined at 770°C for 2 h does not show any diffraction peaks of a-Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16] The vermicular microstructure will lead to large pores and nonuniform packing in green compacts which will trigger differential densification, reduce densification rate, and limit the final density of sintered bodies during sintering. 11-16 a-Al 2 O 3 nucleation from transition aluminas will lead to exaggerated grain growth and a vermicular microstructure (a catenulate and/or reticular microstructure of many primary particles sintered or agglomerated together).…”
Section: Introductionmentioning
confidence: 99%